A framework for local production of a low cost plastic injection mould system (2011)
"The development of a framework for the local production of low-cost injection moulds, using inputs and technical skills available within a typical Nigerian city is the focus of this study. The plastic casing of an auto-battery has been used as the case study product. Product analysis of the casing and casing mould were carried out to identify features amenable to simplification. For the injection mould design an injection pressure of 83MPa was used for the strength of material analysis. Materials availability survey and analysis were carried at the multipurpose metaI and machinery market located in Agodi, Ibadan, Oyo State, Nigeria. A survey of metal fabrication related skills was carried out in the same market to identify artisans with skills relevant to the proposed production processes. A production process framework supportable by the identified local skills- and materials was thereafter developed. Scrap medium carbon flat sheet was identified as a suitable material. Oxy-acetylene welding was identified as suitable for cutting while arc welding was found adequate for joining. The local artisans were found to be capable of producing the required product if given close supervision. An exploratory evaluation of the mould system was carried out using an improvised low pressure manually operated injection mould. Test, using locally available recycle plastic materials, indicated better plastic formation with a homogeneous polypropylene plastic than heterogeneous polypropylene plastic. It is concluded that plastic mould system is feasible for local fabrication. "